DEVELOPMENT OF SIMULATED MODEL HEAT-CONDUCTING FOR AUTOMATION SYSTEMS CONTROL BY THERMAL FURNACES - Zinchenko, Vladimir; Ivanov, Viktor; Nesterenko, Tatiana; Kayukov, Yurii (Scientific Journal "Metallurgy", 2021)
Absence of the instrumental means for direct estimation of thermal state of metal inheat-treating furnaces generated necessities application of mathematical models which arebased on use of classical differential heat-conduction equation in partial derivatives. Howeverpresence of essential dependence thermophysical properties of metal from temperature leadsto non-linearity equation of heat-conducting. The subsequent analytical solution of equation withuse of simplifications and assumptions is accompanied by considerable inaccuracies at definitionof a distribution function determination for metal in space and in a time. Numeral methodsof solution of the specified equation with application of finite-difference schemes do not allow tooffer the recommendation for rational temperature-time modes of selection of high-heat treatmentfew the studied and new brands of steels. The engineering model heat sharing in the metalbodies, offered by J.D. Semikin is known. According to this a solid body, which heat up thermally,represent as n layers with equal temperature and thermophysical properties. At warmthsupply to such body there is a consecutive heat of the designated layers. At a significantamount of these layers in a massive body such engineering model comes nearer to the systemcontinuously dispense in space. Computer representation of such system is a simulated modelof heating of infinite length plate which can be implemented by means of application package of«Mat Lab 6.5 SP1\7+Simulink 5/6» programs, which are specially dedicated for analogoustasks. Simulation results confirm a possibility of the solution of tasks for working out of temperature-time modes at metal high-heat treatment, and also selection of optimal control algorithmsfor high-heat thermal furnace.